Effect Of Inflation, Exchange Rates, And Trading Volume Activity On Stock Price Indices During The Covid-19 Pandemic On Companies In The Basic Industry And Chemical Sectors - Ervina, Nelly; Azwar, Khairul; Susanti, Elly; Dewi Nainggolan, Christine (Publisher Cv. Inara, 2022)
Covid-19 has an impact on the economy, where ADB decreased with estimates in Asian Developing Countries by 3.0 ppts to 2.2%, and for ASEAN by 3.7 ppts to 1.0% (ASEAN, 2020). In addition, one of the indicators that shows that the occurrence of stock market movements, can be seen through the country's stock price index. The Composite Stock Price Index (JCI), which is one of the benchmarks for the Indonesian stock market, on March 5, 2020 was at 5,638.13 and experienced a low on March 24, 2020 at 3,937.63. This study aims to determine the effect of inflation, exchange rate, and TVA on the stock price index in the basic and chemical industry sectors, which in this case uses data in the period January 2020 -June 2022, namely the period where the stock price index of the basic industry and chemical sectors shows a downward trend in April 2020 and November 2020. The sampling technique used in this study was purposive sampling samples so that 64 Companies in the Basic and Chemical Industries Sector were obtained listed on the IDX. The data analysis technique used in this study uses descriptive statistical analysis to describe the data that has been collected. The results of the study for the F test showed that inflation, exchange rates and TVA had a positive and significant effect on the stock price index. While the results of the t-test show that inflation has a positive and insignificant effect, the exchange rate has a positive and significant effect on the stock price index, and TVA has a negative and insignificant effect on the stock price index.